Remembering Migration
XIX, 357 p. 8 illus.
Keywords: This book provides the first comprehensive study of diverse migrant memories and what they mean for Australia in the twenty-first century. Drawing on rich case studies, it captures the changing political and cultural dimensions of migration memories as they are negotiated and commemorated by individuals, communities and the nation. Remembering Migration is divided into two sections, the first on oral histories and the second examining the complexity of migrant heritage, and the sources and genres of memory writing. The focused and thematic analysis in the book explores how these histories are re-remembered in private and public spaces, including museum exhibitions, heritage sites and the media. Written by leading and emerging scholars, the collected essays explore how memories of global migration across generations contribute to the ever-changing social and cultural fabric of Australia and its place in the world. .